Study of Dimethyl Sulfoxide Effect on Thermal Denaturation of Human Hemoglobin Prior to and after Low Temperature Exposure - Govorova, Yuliya S. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):181.